(untitled) (Research, Society and Development, 2020)
Objective: The aim of this study was to identify the impact of rheumatoid arthritis on the occupational performance of activities of daily living and instrumental activities of daily living and on the quality of life of the patient. As well as, check the perception of the same, about the activities that potentially cause greater pain and fatigue when performed. Method: The cartographic method was chosen for its quanti-qualitative dimension. The study was carried out in the city of Rio de Janeiro, in the Municipal Primary Health Care Network, and the Functional Capacity Assessment, Pain Self-efficacy Questionnaire and Quality of Life Questionnaire- SF-36A were used to collect data. Results: 10 patients with rheumatoid arthritis participated in the study and it was identified that this disease has a great impact on the functional capacity and quality of life of clients generating multiple complications for the occupational performance of the activities routine, of work and leisure, which affects the performance of the Activities of Daily Life linked to self-care, the Instrumental Activities of Daily Life, such as shopping, using a telephone, taking care of the house among others, In addition to diminishing their work capacity causing constant absence caused by pain and fatigue. Conclusion: the therapeutic and educational approach of Joint Protection and Energy Conservation supports for greater control of the symptoms of the disease prevents diseases such as the installation of deformities in the wrist joints, hands and feet, helping to improve quality of life and functional capacity.